Quaternary - MDPI (MDPI, 2026)
Quaternary is an international, peer-reviewed, open access journal that covers all aspects within quaternary science, embracing the whole range of scientific fields related to geological, geographical, biological, physical, chemical, environmental and human sciences. The journal is published bimonthly online by MDPI.
Keywords: Ciencias de la Tierra (Cuaternario); Revistas depredadoras; Predatory journals